2007
DOI: 10.1007/s11116-007-9137-5
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of the determinants of bicycle mode share for the journey to work using census data

Abstract: A model is presented that relates the proportion of bicycle journeys to work for Smaller proportions cycle in wards with more females and higher car ownership.The physical condition of the highway, rainfall and temperature each have an effect on the proportion that cycles to work, but the most significant physical variable is hilliness. The proportion of bicycle route that is off-road is shown to be significant, although it displays a low elasticity (+0.049) and this contrasts with more significant changes usu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
235
3
11

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 353 publications
(287 citation statements)
references
References 14 publications
17
235
3
11
Order By: Relevance
“…Parkin et al (2008) change their mode based on the actual observed weather conditions. There are however some limitations and disadvantages with stated preference surveys which are briefly discussed later.…”
Section: National or Regional Assessments Of Impact Of Weather On Actmentioning
confidence: 99%
See 2 more Smart Citations
“…Parkin et al (2008) change their mode based on the actual observed weather conditions. There are however some limitations and disadvantages with stated preference surveys which are briefly discussed later.…”
Section: National or Regional Assessments Of Impact Of Weather On Actmentioning
confidence: 99%
“…Most of the analysis conducted on the topic falls in one of two categories. Some research is conducted at a very aggregate level and does not include detailed enough weather condition and trip specific characteristics (Dill and Carr 2003, Winters et al 2007, Parkin et al 2008, Berkim et al 2006. Others are very location specific, and while they contain very detailed weather data, they fail to capture the influence of socioeconomic characteristics of trip makers and characteristics of other alternative modes (Brandenburg et al n.a., Thomas et al 2009, Nankervis 1999, Cools et al 2010, Bergstrom and Magnusson 2003, Aultman-Hall et al 2009).…”
Section: 79 Introduction and Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Baltes (1996) and Dill and Carr (2003), in the UK, e.g. Parkin et al (2008) and Waldman (1977), and in the Netherlands, e.g. Rietveld and Daniel (2004).…”
Section: Introductionmentioning
confidence: 99%
“…Using predetermined criteria, each segment of the network is given an LTS rating from 1 to 4, resulting in a map that shows which The value of such infrastructure for increasing cycling is mixed. While many studies have found a positive correlation between levels of bicycle infrastructure and bicycle commuting [15][16][17] others have found little correlation [18][19][20][21]. What is certain is that many cyclists prefer routes with bicycle facilities [22][23][24][25][26][27][28] and bicycle infrastructure encourages non-cyclists to try cycling [14].…”
Section: Audit Instruments For Bicycle Networkmentioning
confidence: 99%